Bergson e a intuição como método - Gomes, Brenda Pereira (2022)
In The Creative Mind, Bergson proposes “to raise intuition to the level of a philosophical method”, insofar as his approach to metaphysics search for a systematic knowledge of things showed that the consequence of applying the method of analysis to solve philosophical problems was to leave aside the concrete reality, which according to him should be understood as movement, multiplicity and duration. Intuition has, indeed, always been a topic for discussion among several areas of knowledge, particularly in philosophy, a domain which gives to this topic careful attention, especially after the Cartesian turn in the field of metaphysics and the theory of knowledge. Bergson, however, in his search for a method that renders possible an insight into reality and the world of life by means of the direct and unmediated knowledge of things that intuition makes possible, has turned intuition into a central topic for his philosophical investigation. He starts with a critique of the tacit admission of reason’s schemas in metaphysics, schemas that deal first with practical life, as well as with a critique of its concept of truth, which leaves aside movement and duration – the very tissue of all reality – and so leads to a crystallization of things in the eternal and in the immovable and immutable. He then finds in intuition a method which can restore to the real its dimension of duration and movement, insofar as it renders possible an immediate perception of reality, without a mediation of the concepts that is proper the method of analysis. Our aim here is to examine, in the first chapter, the problem of intuition as the adequate method for philosophy, insofar as its task is to give metaphysics its direct access to the real; in the second chapter, we will discuss the problem of language in philosophy, insofar as, having blurred the distinction between rigor and precision, philosophy adopted the fixed language of space, that is adequate to the needs of common sense, and so more suited to survival than to reflection and the knowledge of reality itself; and finally, in the third chapter, we will approach Bergson’s theory of duration, insofar as it is fundamental for the concept or the real in metaphysics. In this study, we will mainly address his works: Introduction to Metaphysics (1903), the two introductions of The Creative Mind (1922) and the conference entitled Philosophical Intuition (1911), works in which these concepts appear for the first time, or in a more clear light. We are also going to resort to commentators such as Gilles Deleuze, Bento Prado Júnior and Franklin Leopoldo e Silva, who deal with intuition as a central concept to an investigation of the proper philosophical method in Bergson. We intend, in the course of this work, to show that, according to Bergson, it is through intuition that we can apprehend the movement of duration that is constitutive of reality, and so that it is intuition that can provide a method par excellence for developing a true metaphysics.